Динамічна адаптація складності у відеоіграх - Сєрокуров, Д. О. (ХНУРЕ, 2025)
This scientific work analyzes dynamic difficulty adaptation (DDA), a technique that changes the difficulty of a game in real time based on player performance. DDA helps engage players by balancing challenge and avoiding frustration or boredom. The system adjusts enemy characteristics, resource availability, and AI behavior using analysis of player data.
Keywords: відеогра; dynamic difficulty adaptation (DDA)